The genus Struthiochenopus (Gastropoda, Aporrhaidae): new Miocene records from southern Chile. (January 2014) - Nielsen, Sven N.; Encinas, Alfonso
Abstract : The marine gastropod genus Struthiochenopus appears first in the late Cretaceous of the Antarctic Peninsula. Until the Oligocene only one or two species were extant at the same time. This changed drastically in the early Miocene when at least three species were living coevally in southern South America. A possible fourth early Miocene species, Struthiochenopus sp., is known from Ipún Island, Chile, but its identification remains unclear. Another taxon, S. echtleri new species, described from Neogene deposits of Mocha Island, Chile, has no precise age available but it is likely the latest survivor of the genus.